THE EFFORTS OF INCREASING PGMI STUDENTS CAPACITY IN PREPARING LESSON PLANS (RPP) OF SCIENCE LEARNING THROUGH INDIVIDUAL LESSON - Nanang Purwanto (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2018)
This study aims to improve teacher education ability students of Islamic Elementary Schools Teacher Education (PGMI) in preparing the lesson plans science teaching materials of Islamic Elementary School (MI) and elementary school (SD) through individual instruction. The subjects were students PGMI class D, E and F the 5th semester of the school year 2016/2017 in IAIN Tulungagung, totaling to 112 people. Data collection techniques with interviews and scientific discussion. The results showed improvement in terms of understanding the science lesson planning materials of SD/MI. Improving the ability of preparing lesson plans (RPP) from cycle 1 to cycle 2 with details as follows: (1) the students are able to formulate learning indicators by in cycle 1 was 43.3% and in cycle 2 was 89%; (2) the students are able to formulate learning objectives by in cycle 1 was 13.3% and in cycle 2 was 92%; (3) students are able to choose and organize learning materials systematically in cycle 1 by 39.3% and in cycle 2 by 92.3%; (4) students are able to determine the appropriate method of learning that is in cycle 1 was 85% and in cycle 2 of 92%; (5) students are able to describe the learning method in the form of learning steps that is in cycle 1 of 82,3% and in cycle 2 equal to 93,67%; (6) students are able to choose learning resources and learning media that is in cycle 1 of 82% and in cycle 2 by 90%; (7) students are able to develop assessment techniques in cycle 1 of 45.3% and in cycle 2 was 89.3%.